2005
DOI: 10.1016/j.rmed.2004.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inhalation of thermal water on airway inflammation in chronic obstructive pulmonary disease

Abstract: Thermal water inhalations have been traditionally used in the treatment of upper and lower chronic airway diseases. However, the benefit and the mechanism of this treatment have not been properly assessed. To determine whether inhaled salt-bromide-iodine thermal water improves lung function, quality of life and airway inflammation, 39 patients with chronic obstructive pulmonary disease (COPD) were randomly assigned to receive 2-weeks inhalation treatment with thermal water (active, no. = 20) or normal saline (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 21 publications
(21 reference statements)
5
23
0
Order By: Relevance
“…This result is in line with our previous observations that variables related to health perception are more sensitive than functional indexes to detect effects of treatment with TW [4]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is in line with our previous observations that variables related to health perception are more sensitive than functional indexes to detect effects of treatment with TW [4]. …”
Section: Discussionsupporting
confidence: 93%
“…We confirmed that EBC LTB 4 concentrations are elevated in COPD. However, the results do not provide evidence that the reduced proportion of neutrophils in induced sputum after TW treatment [4] is due to decreased LTB 4 concentrations. Caution should be shown in the interpretation of LTB 4 data because LTB 4 concentrations in EBC exhibited high variability.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The PEF value in patients with bronchial diseases have increased significantly (Table 2), whereas other spirometric parameters in both bronchial and alveolar diseases have been found increased not significant after treatment. Pellegrini et al [5] have found not significantly changes in lung function after 2 weeks of treatment with salt-bromide-iodine thermal water in COPD patients. In our study, when we analyzed the group of patients with objective airflow obstruction (FEV 1 /FVC < 0.7), the index FEV 1 /FVC increased significantly after thermal treatment compared to baseline values before (Table 3), but the reliability of this improvement is debatable due to the small number of subjects (N = 14).…”
Section: Discussionmentioning
confidence: 94%
“…Many scientists think that particular composition of this thermal water plays a useful anti-inflammatory and sedative purifying action on the mucous membranes of the respiratory apparatus: aerosol tiny particels are vaporized and inhaled by the subjects, pass through respiratory tract, giving relief to nose, throat, bronchus, lungs, and larynx. In the literature there are only few works that study the effect of inhalation of salt-bromideiodine thermal water on airway inflammation in patients with lung diseases such as chronic obstructive pulmonary disease (COPD) [5,6]. Moreover, despite its widespread use, much uncertainty exists about the indications and therapeutic mechanisms of thermal water inhalations in the treatment of respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%